Caracterização radiométrica de ácidos fosfóricos e seus produtos industriais - Conceição, Fabiano Tomazini da [UNESP]; Bonotto, Daniel Marcos [UNESP] (My University, 2011)
The addition of phosphoric acids and their (by)products became a common practice in areas like metal treatment, detergent production, water and effluent treatment, as well by food, beverage and pharmaceutical industries. The phosphoric acids exhibit different radionuclides activity concentration, being important to evaluate the implications for the human and animal health. The 238U concentration in almost all raw acid phosphoric are within the worldwide range and the mean exposure rate for the filtration cake is 10 nGy/h, which is mainly attributed to 40K. The results obtained for total and (bio)available uranium concentration in filtration cake indicate that only 40% is (bio)available for plants. The radionuclides present in phosphoric acid food grade and filtration cake do not raise their concentration in human food chain or soils to harmful levels, consequently, not offering hazard to the ecosystem and animal or human health.

A adição de ácidos fosfóricos e seus produtos derivados tornou-se uma prática comum em várias áreas como tratamento de metais, produção de detergentes, tratamento de águas e efluentes, bem como em indústrias alimentícias, de bebidas e farmacêuticas. Os radionuclídeos nos ácidos fosfóricos estão presentes em diferentes concentrações atividade, de maneira que é importante avaliar as implicações para a saúde humana e animal. A atividade de 238U no ácido fosfórico bruto praticamente está inserida no intervalo de variação global e a taxa de exposição média associada ao material filtrado corresponde a 10 nGy/h, a qual é atribuída principalmente ao 40K. Os resultados obtidospara a concentração total e biodisponível de urânio no material filtrado indicam que apenas 40% encontra-se disponível para as plantas. Os radionuclídeos presentes no ácido fosfórico de grau alimentar e material filtrado não contribuem para a elevação da radioatividade na cadeia alimentar humana ou solos até níveis perigosos, portanto, não oferecem riscos ao ecossistema e saúde humana e animal.
Radiometric characterization of phosphoric acids and their industrial products
Keywords: Environmental hazards; Phosphoric acids and (by) products; Radionuclides; bioavailability; concentration (composition); detergent; effluent; environmental hazard; filtration; food chain; food industry; industrial production; pharmaceutical industry; pollution exposure; public health; radionuclide; uranium isotope; water treatment; Animalia